Kelestarian Langkawi Geopark: penglibatan komuniti Kuala Teriang, Langkawi. - Nur Hafizah Yusoff,; Rahimah Abdul Aziz, (Universiti Kebangsaan Malaysia, 2010)
In June 2007, Langkawi was conferred the Geopark status by United Nations Educational, Sientific and Cultural Organization (UNESCO). Langkawi Geopark is the only geopark in Southeast Asia and the 52nd geopark around the world. ‘Geopark’ can be regarded as a new brandname given to Langkawi, that could be used to promote Langkawi to the tourists and the world in general. Generally, any area can be recognised as a geopark, but on condition that the area possesses several geoheritage characteristics and significant geological landscapes. Another important component of geopark is the local community participation. This is so because members of the community will contribute towards ensuring sustainability of geopark through its conservation and ecotourism activities. This research is about community participation as an important component of Langkawi Geopark. This research conducted in Kampung Kuala Teriang, Langkawi was generally to identify the participation of Kuala Teriang community in ensuring the success and subsequently the sustainability of Langkawi Geopark. Survey method was employed as well as nonstructured interview and non-participant observation for data collection and information. A total of 200 people were sampled to be respondents using stratified and snowball sampling techniques. Only some of the research findings are presented and discussed in this research note. The findings include community participation in the local economic activities such as Fisheries Source Management Community (Komuniti Pengurusan Sumber Perikanan (KPSP)) and Woman Economic Group (Kumpulan Ekonomi Wanita (KEW)).